Do chronic noncommunicable diseases modify the macronutrient composition of human milk?. (17th February 2021) - Amaral, Yasmin; Marano, Daniele; Abranches, Andrea; Silva, Leila; Nehab, Sylvia; Costa, Ana Carolina; Moreira, Maria Elisabeth
Abstract: This study aims to evaluate the impact of excess body weight, diabetes mellitus, and hypertension on the nutritional composition of human milk. This cohort study was conducted at a tertiary public health unit in the city of Rio de Janeiro from March 2016 to February 2018. The data were collected in two stages (96 hours and one month after delivery). The macronutrients (carbohydrate, protein, lipid) and total energy were determined using the MIRIS ® equipment. The level of significance was 5%. Higher protein content was observed in the nutritional composition of colostrum in women with diabetes mellitus. A higher protein and energy content was observed in the milk of mothers with excessive body weight. The energy content was higher in the milk of mothers with excessive body weight. Increased protein content in the human milk of women with excessive body weight or diabetes.